1996
DOI: 10.1161/01.hyp.27.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone–Related Protein Inhibits Endothelin-1 Production

Abstract: The effect of human parathyroid hormone-related protein, a powerful vasodilator, on endothelin-1 production in cultured bovine pulmonary arterial endothelial cells was studied. Treatment with parathyroid hormone-related protein(1-34) at concentrations of 10(-9) to 10(-6) mol/L for 24 hours caused dose-dependent suppression of the secretion of endothelin-1, with maximal suppression at 10(-7) mol/L to 74% of the control value. This inhibitory effect was completely abolished by coincubation with 100 ng/mL pertuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…Along with this assumption, both a marked increase in cAMP and a small increase in cGMP were seen in rabbit aortic strips during PTH-induced relaxation (Nickols & Cline 1987). Moreover, the vasodilating property which hPTHrP(1-34) has shown may be mediated, in part, through its inhibitory effect on endothelin-1 production, which is probably mediated through NO and cGMP in pulmonary arterial endothelial cells (Jiang et al 1996).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Along with this assumption, both a marked increase in cAMP and a small increase in cGMP were seen in rabbit aortic strips during PTH-induced relaxation (Nickols & Cline 1987). Moreover, the vasodilating property which hPTHrP(1-34) has shown may be mediated, in part, through its inhibitory effect on endothelin-1 production, which is probably mediated through NO and cGMP in pulmonary arterial endothelial cells (Jiang et al 1996).…”
Section: Discussionmentioning
confidence: 82%
“…Parathyroid hormone-related peptide (PTHrP), initially identified as a factor responsible for malignancy-associated hypercalcemia (Philbrick et al 1996), has subsequently been demonstrated not only in tumor tissues but also in a number of normal fetal and adult tissues including vascular endothelial cells (Ishikawa et al 1994, Rian et al 1994, Jiang et al 1996 and smooth muscle cells of non-vascular and vascular origin (Burton et al 1994, Philbrick 1996. The role of PTHrP is increasingly recognized as an important autocrine/paracrine hormone in regulating physiological functions, such as local modulation of microcirculation, whereas PTH only mimics the vascular action of PTHrP.…”
Section: Introductionmentioning
confidence: 99%
“…The dose of thrombin used for this study (10 U/ml), which we also used in a previous study, 27 exerted almost maximal responses in ET-1 secretion in all of the bovine and human endothelial cell types. Moreover, the time-course of expression of ET-1 mRNA in the present study was comparable with that of our previous investigation.…”
Section: Electromagnetic Fields Inhibit Endothelin-1 Productionmentioning
confidence: 94%
“…Moreover, the time-course of expression of ET-1 mRNA in the present study was comparable with that of our previous investigation. 27 An interesting observation was the opposite effects of EMF on the basal secretion of ET-1 in different cultured endothelial cell types. EMF radiation substantially enhanced ET-1 secretion in HAEC, but considerably suppressed it in HUVEC.…”
Section: Electromagnetic Fields Inhibit Endothelin-1 Productionmentioning
confidence: 99%
“…Estos efectos producirían una marcada elevación de la presión de los vasos sanguí-neos pulmonares exacerbando la hipoxemia, causando finalmente falla cardíaca, shock y síndrome de distress respiratorio agudo. Esta condición agravaría la vasocons- Modelos teóricos atribuyen un rol protagónico a la TP [81][82][83] , la que produce un desbalance en el tono de la vasculatura pulmonar al inhibir una serie de agentes vasodilatadoras del endotelio, disminuyendo la síntesis de óxido nítrico, y en consecuencia favoreciendo la actividad de vasoconstrictores locales como la endotelina-1 84 . También se ha postulado que la TP, por un mecanismo de sensibilización de las células endoteliales de la vasculatura pulmonar, produciría un aumento en los niveles de AMPc resultando en vasoconstricción de estos vasos 85 .…”
Section: Fisiopatologíaunclassified